The Role of Feed in Aquatic Laboratory Animal Nutrition and the Potential Impact on Animal Models and Study Reproducibility - Brenes Soto, Andrea (2020)
Feed plays a central role in the physiological development of terrestrial and aquatic animals. Historically, the feeding practice of aquatic research species derived from aquaculture, farmed, or ornamental trades. These diets are highly variable, with limited quality control, and have been typically selected to provide the fastest growth or highest fecundity. These variations of quality and composition of diets may affect animal/colony health and can introduce confounding experimental variables into animal-based studies that impact research reproducibility.